Immunogenicity and Efficacy of Insulin Glargine Biosimilar Ezelin versus Originator Insulin Glargine in Patients with Type 2 Diabetes - Tarigan TJE; Dwijayanti A; Setyowati S; Louisa M (Diabetes, Metabolic Syndrome and Obesity, 2021)
Tri Juli Edi Tarigan,1 Adisti Dwijayanti,2 Susie Setyowati,3 Melva Louisa4 1Division of Endocrinology and Metabolism, Department of Internal Medicine, Dr. Cipto Mangunkusumo National Referral Hospital, Faculty of Medicine, Universitas Indonesia, Jakarta, Indonesia; 2Department of Medical Pharmacy, Faculty of Medicine, Universitas Indonesia, Jakarta, Indonesia; 3Division of Endocrinology, Department of Internal Medicine, Gatot Soebroto Presidential Hospital, Jakarta, Indonesia; 4Department of Pharmacology and Therapeutics, Faculty of Medicine, Universitas Indonesia, Jakarta, IndonesiaCorrespondence: Tri Juli Edi TariganDivision of Endocrinology and Metabolism, Department of Internal Medicine, Dr. Cipto Mangunkusumo National Referral Hospital, Faculty of Medicine, Universitas Indonesia, Jakarta, IndonesiaTel +62 21-3907703Email tri.judi@ui.ac.idPurpose: To compare the immunogenicity and efficacy of insulin glargine biosimilar Ezelin (EZL) versus originator insulin glargine Lantus (LAN) as a reference basal insulin in patients with type 2 diabetes (T2D).Patients and Methods: This was a randomized, multicenter, open-label, 24-week study in insulin-naïve patients with T2D, with HbA1c of > 7.0%. We randomly assigned 133 eligible patients to receive either EZL or LAN. Baseline characteristics, including insulin autoantibody (IAA), zinc transporter 8 (ZnT8) antibody, HbA1C, fasting plasma glucose (FPG), 2-hour postprandial plasma glucose (2hPPG), AST, ALT, BUN, eGFR, and oral antidiabetic drugs, were obtained before starting insulin treatment. After starting treatment, insulin dose was titrated to achieve FPG target along with oral antidiabetic drugs. Patients were given home glucometer and assisted to record plasma glucose measurement and adverse event (AE). Every month, patients came to the diabetes clinic and performed a regular physical examination and intensifying treatment if needed. Out of the 133 randomized patients, only 122 completed the study and can be examined for their IAA and ZnT8 after 6 months of treatment. The study was registered in clinicaltrials.gov, NCT03352674.Results: There is a similar proportion of patients with changes of IAA from baseline: 1 out of 58 (1.7%) patients receiving EZL versus 1 out of 64 (1.6%) patients receiving LAN (p = 1.000). One patient in the EZL group (1.7%) versus none in the LAN group experienced a change of ZnT8 antibody from baseline. Similar glucose control in EZL versus LAN was determined by the change in HbA1c, FPG, and 2hPPG (− 2.0%, − 67.46 mg/dL, and − 76.51 mg/dL in the EZL group versus − 1.7%, − 58.11 mg/dL, and − 70.03 mg/dL in the LAN group). There were six events of documented hypoglycemia in the EZL group versus five events in the LAN group. No patients experienced diabetic ketoacidosis during the study.Conclusion: Overall, insulin glargine biosimilar EZL and originator insulin glargine LAN have shown a similar immunogenicity profile, as well as efficacy in providing glucose control and safety findings in T2D populations.Keywords: biosimilar, insulin autoantibody, zinc transporter 8 antibody, hyperglycemia